Collisions of difference: Teaching gender and sexuality in a conservative and religious culture. Issue 1 (1st April 2022) - Ingersoll, Alicia R; Cook, Alison
Gender and sexuality have been at the forefront of societal debate in recent years with various legal battles concerning LGBT rights and religious liberties taking center stage. Shifts in attitudes and gains in legal protections have served to entrench conservative religious beliefs and to perpetuate generational "bitter" knowledge. This study seeks to understand the types of beliefs brought into the classroom by students and to examine the role of religious socialization in shaping and maintaining problematic beliefs in the context of learning new discordant knowledge. The data demonstrate that students bring "bitter" or problematic knowledge into the classroom, which serves as an obstacle to engaging in critical inquiry. We explore how the educational technique of engaging in pedagogies of discomfort invites students to see things differently and to examine how the religious institution has shaped their beliefs and values. We conclude with the call for educators to create authenticity and safety through sharing in self-examination and presenting their own vulnerability within the course.